2013
DOI: 10.1155/2013/794202
|View full text |Cite
|
Sign up to set email alerts
|

Equalizer's Use Limitation for Complexity Reduction in a Green Radio Receiver

Abstract: is work is about reducing energy consumption in the receiver chain by limiting the use of the equalizer. It is to make the radio receiver aware of its environment and able to take decision to turn on or off the equalizer according to its necessity or not. When the equalizer is off, the computational complexity is reduced and the rate of reduction depends on the percentage of time during which this component is disabled. In order to achieve this scenario of adapting the use of the equalizer, we need to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…To estimate the angle of arrival θ we performed in Bourbia et al [] a study on different techniques of estimation, and we concluded that the algorithm of CAPON is the best in our case for the compromise between the minimum estimation error and the minimum computational complexity. Now by following our decision‐making method of statistical modeling, we characterize statistically the observations ()falsex̂θ1,..,falsex̂θn of θ .…”
Section: Decision‐making Methods By Statistical Modeling Of the Radio mentioning
confidence: 83%
“…To estimate the angle of arrival θ we performed in Bourbia et al [] a study on different techniques of estimation, and we concluded that the algorithm of CAPON is the best in our case for the compromise between the minimum estimation error and the minimum computational complexity. Now by following our decision‐making method of statistical modeling, we characterize statistically the observations ()falsex̂θ1,..,falsex̂θn of θ .…”
Section: Decision‐making Methods By Statistical Modeling Of the Radio mentioning
confidence: 83%
“…We consider here a receiver with an equaliser that can be activated or disabled. The method of learning and decision making that we adopt is based on a statistical approach that we developed in our previous work . Our idea is to statistically model and characterise the radio environment using some techniques of the statistical inference like statistical estimation and statistical detection.…”
Section: Green Cognitive Radio Scenariomentioning
confidence: 99%
“…Based on these channel indicators and on their statistical characteristics, we can evaluate the current state of the channel and then decide if the equaliser is necessary in this case or not. The use of the statistical aspect of the channel quality indicators allows taking into account the estimation errors of these metrics in the decision making system, which affect the decision performance .…”
Section: Green Cognitive Radio Scenariomentioning
confidence: 99%
See 2 more Smart Citations